Peran Masyarakat Dalam Mewujudkan Desa Wisata: Studi di Kampung Nelayan, Tanjung Binga, Kabupaten Belitung - Junaid, Ilham (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2020)
This paper aims at analyzing the opportunities for managing and developing Kampung Nelayan as Desa wisata tourism village); 2) recommending efforts or steps to optimize the role and function of the community in managing tourism village. This paper employed a qualitative methodology in understanding and analyzing the actual condition of Kampung Nelayan through interviews and observation. The research was done in 2019 by visiting the research area. The research shows that Kampung Nelayan in Belitung Regency has the potential as a tourism village. Cultural tourism, with an emphasis on community-based rural tourism, is essential to attract visitors. The hospitality of the local people is an important factor in supporting the implementation of community-based rural tourism. This paper proposes the role of the local community for the implementation of a tourism village, including the initiator, executor, and evaluator. The local community, as the stakeholder of tourism, may implement stages (functions) such as socialization, economic, participation, and mutual support to achieve the goals of tourism village.